Milk somatic cell count of selenium and vitamin E supplemented cows - Paschoal, Juliana Jorge; Zanetti, Marcus Antonio; Cunha, José Aparecido (Brazilian Journal of Veterinary Research and Animal Science, 2006)
Selenium and vitamin E are important antioxidants for cells and tissues protection acting directly as a support for the udder health. This experiment was designed to evaluate the influence of prepartum selenium and vitamin E supplementation on milk somatic cell counts of Holstein cows during summer period. Eighty animals were allocated into four treatments: control; supplementation with 2.5 mg Se/day; supplementation with 1000 IU vitamin E/day and supplementation with 2.5 mg Se/day + 1000 IU vitamin E/day. The supplementation started thirty days prior to probable parturition date until parturition. Forage and concentrate samples were taken every fifteen days for chemical and selenium analyses. Blood samples were taken before starting supplementation, right after parturition, thirty and sixty days after it to determine the selenium serum levels. Milk samples were taken to determine SCC. Selenium supplemented cows had higher serum selenium concentration compared with control group (P;0.05) SCC up to 12th week of lactation.